Membangun Mindset Entrepreneur : Kunci Sukses di Era Digital - Gresia Monika Sinaga; Rendi Rendi; Yosia Belo (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the importance of developing an entrepreneurial mindset as a key to success in facing challenges and opportunities in the digital era. The rapid development of information and communication technology presents many opportunities for individuals to start businesses, especially for the younger generation. This study highlights the important characteristics of an entrepreneurial mindset, including resilience, creativity, and flexibility, which are the basis for an entrepreneur to respond to challenges and take risks. Sellers who have a positive mindset are able to identify opportunities where others see problems and adapt to market changes. In addition, overcoming the fear of failure and having strong motivation are described as important factors in starting a business. This article uses a literature study method to analyze previous theories and research on entrepreneurship and the entrepreneurial mindset, providing insights and strategies for prospective entrepreneurs to succeed in an increasingly competitive business world.